2011
DOI: 10.1007/s00330-011-2215-2
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations and clinical value of N-acetyl resonances in ovarian tumours using in-vivo proton MR spectroscopy at 3T

Abstract: Proton MR spectroscopy with quantitative evaluation of the metabolite at 2 ppm concentration, which may suggest the presence of mucinous material containing N-acetyl mucinous compounds, can provide helpful information in distinguishing mucinous and non-mucinous ovarian tumours. Key Points • MR spectroscopy helps distinguish mucinous from non-mucinous ovarian tumours. • High N-acetyl resonance at 2 ppm is observed in ovarian mucinous tumours. • Thus MR spectroscopy could improve management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Proton MR spectroscopy may identify the presence of mucinous material containing N-acetyl mucinous compounds, and can provide helpful information in distinguishing mucinous and nonmucinous ovarian tumours. Therefore, MR spectroscopy helps to diagnose the subtypes of ovarian tumours and may contribute to the adequate treatment, thus improving management of these patients [ 25 ].…”
Section: Approach To Adnexal Massesmentioning
confidence: 99%
“…Proton MR spectroscopy may identify the presence of mucinous material containing N-acetyl mucinous compounds, and can provide helpful information in distinguishing mucinous and nonmucinous ovarian tumours. Therefore, MR spectroscopy helps to diagnose the subtypes of ovarian tumours and may contribute to the adequate treatment, thus improving management of these patients [ 25 ].…”
Section: Approach To Adnexal Massesmentioning
confidence: 99%
“…Takeuchi et al . conceded that their results also suggest contamination from other sources. The use of a powerful spectral analysis tool, such as the Quest algorithm, is imperative to allow contributions from overlapping spectral metabolites to be quantified.…”
Section: Discussionmentioning
confidence: 96%
“…However, one possible contaminant may simply be polyunsaturated fatty acids (41). In addition, Takeuchi et al (42) suggested that a peak detected at approximately 2 ppm in a 1 H MRS study of ovarian tumours could be attributed to N-acetyl mucinous compounds (i.e. those containing the glycosylated protein mucin).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAA is reverberant at 2.0 ppm, it is called neuronal marker [15]. Some studies [16] detected NAA metabolites in both solid and cystic elements of the mucinous cystadenoma. A study conducted by El Sorogy et al (2012) also detected the NAA signal in all cases of mature cystic teratomas, denoting the presence of a neural component (ectodermal tissue) [4].…”
Section: Discussionmentioning
confidence: 99%